2022
DOI: 10.14744/bej.2022.58234
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Ophthalmology Residency Education

Abstract: In December 2019, there were some reports revealed that the previously unknown virus was causing pneumonia in Wuhan, a city in Eastern China (1). February 11, 2020, the World Health Organization (WHO) declared the official name as "Coronavirus disease 2019 (COVID-19)," shortened version; COVID-19. March 11, 2020, the first COVID-19 case was detected in Türkiye (2) and March 17, 2020, the first COVID-19-related death occurred (3). At the time of writing this study, there have been 510,270,667 confirmed cases an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Several studies have reported the negative effects of the COVID-19 pandemic on the mental health of healthcare professionals worldwide 4 5. Ophthalmology residents and faculty have also reported increased stress, anxiety and depression due to the pandemic 6–8. In addition, the economic crisis in Lebanon had a significant impact on the healthcare sector, leading to shortages of supplies and financial difficulties for both hospitals and healthcare providers 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported the negative effects of the COVID-19 pandemic on the mental health of healthcare professionals worldwide 4 5. Ophthalmology residents and faculty have also reported increased stress, anxiety and depression due to the pandemic 6–8. In addition, the economic crisis in Lebanon had a significant impact on the healthcare sector, leading to shortages of supplies and financial difficulties for both hospitals and healthcare providers 9…”
Section: Introductionmentioning
confidence: 99%
“…4 5 Ophthalmology residents and faculty have also reported increased stress, anxiety and depression due to the pandemic. [6][7][8] In addition, the economic crisis in Lebanon had a significant impact on the healthcare sector, leading to shortages of supplies and financial difficulties for both hospitals and healthcare providers. 9 Moreover, the Beirut explosion in August 2020 further exacerbated the challenges faced by healthcare professionals in Lebanon.…”
Section: Introductionmentioning
confidence: 99%